Proto-Karen final stops - Benedict, Paul K. (2024)
Final *-0, *-n and *-m must be set up for Proto—Karen (PK) on the basis of their maintenance in Pa-'o (STC: 142 and fn. 384; *-n only after high vowels) but Pa-o, Pwo and Sgaw all regularly have -? corresponding to PTB final stop (STC: 144 ff.). It now appears, however, that final *-k, *-t and perhaps *-p should also be reconstructed at the PK level, paralleling the final nasals.